2007
DOI: 10.5897/ajb2007.000-2404
|View full text |Cite
|
Sign up to set email alerts
|

Development of amino resins for emulsion paint formulation: effect of aldelhydic group and degree of substitution

Abstract: In our continuous effort to develop a paint binder from amino resins, amino resins from different aldehydic groups were synthesized to produce urea, formaldehyde (UF), urea acetaldehyde (UA), urea proparaldehyde (UP) and urea butaldehyde (UB) at different degree of substitution (Mono -tetra). Some physical properties of these resins were evaluated. The viscosity, gel time, density and refractive index of the resins (except UB) were found to increase with increase in alkyl length of the aldehydic group while tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Konstantin V. Lipin 1 , lipinkost@mail.ru Sergey V. Fedoseev 1 , sergey.fedoseev88@gmail.com Denis A. Kizyaev 2 , denis.kizyaev@yandex.ru The relevance of the study is caused by high danger of technogenic emission of formaldehyde into the environment. The main anthropogenic source of formaldehyde is the production of particle board, which uses urea-formaldehyde resins.…”
Section: Technology For Removing Free Formaldehyde From Urea-formalde...mentioning
confidence: 99%
See 1 more Smart Citation
“…Konstantin V. Lipin 1 , lipinkost@mail.ru Sergey V. Fedoseev 1 , sergey.fedoseev88@gmail.com Denis A. Kizyaev 2 , denis.kizyaev@yandex.ru The relevance of the study is caused by high danger of technogenic emission of formaldehyde into the environment. The main anthropogenic source of formaldehyde is the production of particle board, which uses urea-formaldehyde resins.…”
Section: Technology For Removing Free Formaldehyde From Urea-formalde...mentioning
confidence: 99%
“…Их получают поликонденсацией карбамида и формальдегида. Кроме этого, КФ смолы применяют, как эмульсионные краски [2], конденсаторы в электрохимии [3,4], для получения нанопорошков [5] и сорбен-та для удаления загрязнений из сточных вод [6]. В последние годы КФ смолы часто находят применение в агрохимии [7,8].…”
Section: Introductionunclassified
“…Some works can be found in literature dealing with providing formaldehyde‐based resins with some flexibility. Strategies involve introduction of plasticizers, flexible chains, and thermoplastic fillers . In the current work a different approach is followed, based on the incorporation of compounds that act as chain growth blockers.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies involve introduction of plasticizers, 5,6 flexible chains, 7-9 and thermoplastic fillers. [10][11][12][13] In the current work a different approach is followed, based on the incorporation of compounds that act as chain growth blockers. The purpose is to decrease the crosslinking density of the final cured resin, allowing for greater chain mobility and thus higher flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…As the samples were undergoing agitation on the shaker, they were removed one after the other at a predetermined time interval ranging from 0.5 to 24 hours at 30 o C. The solutions were filtered and analyzed for the residual metal ions using AAS (Chamarthy et The effect of pH on the maximum sorption capacity of the metal ions studied were 4 for Cd2+, 6 for Pb2+, and 5 for Fe3+, Cr3+, and Zn2+. The pH of the sorption media is related to the metal sorption -mechanism of the surfaces from the water and reflected the nature of the physicochemical interaction of the ions in solution and nature of the sorption sites (Osemeahon et al, 2007). Therefore, it can be suggested that the differences in the pH optima for different metal mioents aclo uld probably be due to the different solution chemistry of the metal ion (Lee et al, 2009).…”
Section: Determination Of the Effect Of Contact Time On Sorption Capamentioning
confidence: 99%